Intelligent system in micro and small business sales management: a systematic review - Espinoza Cruz, Manuel Alberto (2022)
The study aimed to know how the smart store system improves the sales management of micro and small enterprises between 2016 and 2021. It used an adaptation of the Prisma methodology, which poses a system for evaluating the systematic review of scientific literature on its relationship with the objective and the research question. The databases used were ScienceDirect, Scielo, Scopus and Ebsco. A total of 106 scientific articles were found; and after applying the selection criteria, 40 original studies were obtained. It is concluded that intelligent systems were implemented and developed with the aim of improving sales management, through the new shopping experience allowing an important advantage for customers. It is necessary to point out that in the reviewed studies expose the effectiveness of communication, achieving that these businesses each time improve their products; and thus try to satisfy the needs of current and potential consumers. Therefore, in the research reviewed, it has been found that these systems implemented in micro and small businesses allow reducing costs in the management and online sales processes.